Responsability, endangerment, simulation: judicial practices in a psychiatric hospital, Santa Fe (Delito y Sociedad, 2019)
The article presents the advances of a research developed in a public institution of psychiatric hospitalization of Santa Fe, whose general objective is to investigate how the government of madness take place through the analysis of health care practices and policies in force mental in confinement contexts. Particular emphasis is placed on practices that reveal the juxtaposition between healthcare interventions and custodial interventions. It describes the regulations, policies and current programs that frame the daily dynamics of people in conflict with the criminal law interned in psychiatric institutions. Three types of judicial practices are analyzed: the evaluation of responsibility, the assessment of endangerment, and the evaluation of simulation. It is concluded that the juxtaposition between the penal device and the assistance device, far from constituting a simplistic antagonism, is articulated in such a way that the functions can be inverted between one and other. In addition, the presence of patients in conflict with the criminal law causes modifications in the hospital landscape, which reinforce custodial features and tasks. This indicates that there is currently a process of penitentiarization of psychiatric hospitals.
Keywords: Judicial Practices; Responsibility; Dangerousness; Simulation